The Morphological Characters of Egg and Relationship of Immature Stages of Hermolaus modestus (Heteroptera: Pentatomidae: Eysarcorini): Morphological Characters of Hermolaus modestus (Biological Sciences - PJSIR, 2021)
The paper investigates the biology and structure of egg and different developmental stages from 1st instar to 5th instar of Hermolaus modestus (Distant) (Pentatomidae: Eysarcorini). The experiment was conducted in the laboratory and the species was recognized as plant-sucking pest and mostly recorded on Ocimum basilicum (L.) from different areas of Karachi, Pakistan. The male and female individuals were breed under controlled laboratory condition. The maximum fertility range of Hermolaus modestus was observed 10 to 14 eggs per female and eggs were laid singly on the ventral side of plant leaves near the midrib. The incubation period was completed in 4 to 5 days. Newly emerged nymphs were dark red in colour but later colour changed into brown. The nymph passed through five instars progressively to complete the nymphal period. The first instar completed in 2 to 3 days with its specific characters. The second instar took 6 to 7 days with large clypeus. The third instar having scent gland plates and wing pads, completed in 5 to 6 days. The fourth and fifth instars of H. modestus completed in 5 to 6 and 8 to 9 days with prominent mesonotal and metanotal wing pads, respectively. The total nymphal period varied from 26 to 31 days. The total life cycle showed variation from 30 to 36 days. The total body length of male Hermolaus modestus was recorded as 4.8 mm to 5.0 mm.